Development and Characterization of Biodegradable Polymeric Nanoparticles for Colon Cancer Treatment (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
The current study aimed to assess the cytotoxic potential of doxorubicin (DOX) loaded nanoparticles (NPs) for effective colon cancer targeting. Poly-caprolactone (PCL) was used to make the NPs, and PCL was then conjugated with hyaluronic acid (HA) and polyethylene glycol (PEG) (HA-PEG-PCL NPs). The developed NPs were used to encapsulate the DOX, which was then tested for stability, in-vitro drug release, cell viability, and entrapment effectiveness. The NPs were manufactured with care, and TEM examinations showed that they were spherical. Zeta potential measurements for HA-PEG-PCL and PCL NPs were 16.4±0.84 mV, -4.9±0.3, and PDI 0.648 and 0.553, respectively, for both formulations. HA-PEG-PCL NPs and PCL NPs were found to have particle sizes of 267±0.5 nm and 142±1.5 nm, respectively. The NPs made using HA-PEG-PCL copolymers demonstrated their ability to continue the release of DOX. While DOX-HA-PEG-PCL NPs released 93.1±2.4% of DOX in 96 hrs, DOX-PCL NPs released nearly 100% of the medication in the same time frame. When the stability was assessed in terms of particle size and %EE, it was discovered that the NPs formulations were more stable at 4±2°C and then 28±2°C. Because HA binds to the overexpressed CD44 receptors on HT-29 cells, the DOX-HA-PEG-PCL NPs demonstrated noticeably more cytotoxicity as a result of better formulation internalization. The controlled drug release behaviour of the proposed nanotechnology showed their potential for colon cancer cell lines.